Atividade leishmanicida e caracterização química da própolis vermelha produzida no estado do Tocantins, Brasil - SOUSA JUNIOR, Marcos Marinho de (2021)
Brazilian red propolis is produced in the Northeast Region of the country by Apis mellifera L. bees and has Dalbergia ecastophyllum as its botanical source. The literature describes propolis antibacterial, antifungal, antitumor, antioxidant, anti-inflammatory, cytotoxic, and antiparasitic activities. The objective of the present study was carrying out a literature review on the chemical composition and leishmanicidal activity of Brazilian propolis by evaluating the leishmanicidal activity and characterizing the chemical composition and palynological profile of red propolis produced in the Brazilian state of Tocantins, a region that has not been mentioned in the literature as a place known for the production of this type of propolis. The first chapter shows a literature survey and discusses studies on evaluation of the chemical composition and leishmanicidal activity of Brazilian propolis found in the following databases: National Library of Medicine (National Institutes of Health, PubMed), Science Direct, Scopus, and Latin America and Caribbean Center on Health Sciences Information. The integrative reviewing method was applied. The search identified 28 articles published between 2004 and 2020 addressing red, green, and brown propolis. Chemical analyses of Brazilian propolis essential oils were carried out by using gas chromatography associated with mass spectrometry or flame ionization and identified the presence of monoterpenes, sesquiterpenes, and phenylpropanoids. Analysis of hydroethanolic extracts were carried out by using high-performance liquid chromatography with UV-Vis detection (HPLC/UV-Vis) and connected to mass spectrometer (HPLC/MS), which identified terpenes, phenolic acids, flavonoids, and benzophenones. Studies that assessed the leishmanicidal activity of Brazilian propolis in different species of Leishmaniawere more abundant between 2007 and 2020 and reported use of hydroethanolic extracts, essential oils, polymeric nanoparticles, and metal complexes in combination with propolis to inhibit promastigote and amastigote forms. The second chapter shows the palynological profile of propolis obtained by applying characterization performed by using HPLC/MS in both positive and negative modes. Botanical analysis identified 22 pollen types that belonged to 15 botanical families, among which Arecaceae, Asteraceae, Fabaceae, Myrtaceae, Melastomataceae, Rubiaceae, and Urticaceae were more frequent. Polliniferous and nectariferous species were identified. However, the palynological profile of Dalbergia ecastophyllum, a species related to production of red propolis in the Brazilian Northeast coast, was not obtained. Mass spectra obtained by using HPLC/MS showed a precursor ion fragmentation pattern compatible with compounds belonging to the classes of isoflavonoids, pterocarpanes, flavanones, chalcones, as well as isoflavones condensed with a chalcone (retusapurpurin). The third chapter shows the results of the evaluation of propolis extracts and fractions regarding leishmanicidal activity against the promastigote form of Leishmania amazonensis and cytotoxicity induced in RAW 264.7 macrophages measured by applying the cell viability method with (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide). Total phenolic content and flavonoid concentration were measured by using UV-vis spectrophotometry, whereas chemical composition was obtained by HPLC/MS. The extracts inhibited promastigote forms, with IC50 ranging from 21.98 to 86.12 µg/mL. The chloroform fraction was the most effective (16.02 µg/mL). Evaluation of cytotoxicity against RAW 264.7 macrophages indicated that red propolis extract and chloroform fraction showed cell toxicity for concentrations equal to or higher than 100 µg/mL. The samples had high total phenolic content and flavonoid concentration for extracts and chloroform fraction, whereas HPLC/UV-Vis showed similar chemical profiles, with identification of the substances formononetin and biochanin A in all samples, which are considered chemical markers. The results allowed to conclude that red propolis produced in the Brazilian state of Tocantins has leishmanicidal potential, low cell toxicity, and high concentrations of phenolic compounds. This is the first study oriented toward characterizing red propolis produced in Brazilian Amazon and will contribute to the development of apiculture in Tocantins based on production and commercialization of this product.